2018
DOI: 10.1080/24740527.2018.1476821
|View full text |Cite
|
Sign up to set email alerts
|

Factors involved in patients’ perceptions of self-improvement after chronic pain treatment

Abstract: Background Patients’ self-reported levels of improvement after having attended a chronic pain management program can provide a subjective rating of how successful they perceive they were at accomplishing their goals in the program. Past studies have demonstrated that successful patients differ from less successful ones on several cognitive–behavioral factors such as coping strategies over physical characteristics such as pain intensity. Aims This study explored factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Patients are motivated to attend pain programs after experiencing limited relief with biomedical methods (40). Results from these satisfaction questionnaires are consistent with previous findings in this program (12,25,27).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients are motivated to attend pain programs after experiencing limited relief with biomedical methods (40). Results from these satisfaction questionnaires are consistent with previous findings in this program (12,25,27).…”
Section: Discussionsupporting
confidence: 91%
“…The SES is used to determine the participant’s perceived performance in the program. The SES was found to be reliable and valid in assessing goal accomplishment in a multidisciplinary chronic pain management program (12,26,27).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the sample of this study was primarily female and Caucasian, which might lead to issues with generalizability and highlight potential issues of program accessibility and barriers to participation. Though the demographics of this sample were comparable to those of similar studies in the region, 40,41 this is an important area for future research, especially in relation to publicly funded programs. Additionally, although the regression models suggest that pain-related outcomes predict the stages of change, this is simply an association and not an assumption of direction or causation.…”
Section: Discussionmentioning
confidence: 67%
“…Second, this could reflect the multitude of other factors that might influence an individual’s perception of change, including recall bias. In individuals with chronic pain, perception of improvement has been shown to be influenced by psychological factors, coping strategies, and general health [ 32 ]. A prior study of individuals with knee OA showed incongruence between patient perception of functional ability and performance-based measurements [ 33 ].…”
Section: Discussionmentioning
confidence: 99%